In the context of mediation, is safeguarding mediator neutrality and party autonomy more important than ensuring a fair settlement?. Issue 2 (11th July 2016) - Chalkey, Katherine; Green, Martin
Abstract : Purpose: This paper aims to explore the appropriate role and approach of mediators and investigate whether mediator neutrality and party autonomy should prevail over mediators' obligations to remain neutral where non-intervention would result in unfair settlements. Design/methodology/approach: The paper arises from polarising and paradoxical opinions of the legitimacy of mediator intervention. This paper relies upon theories proposed in peer-reviewed journals, together with secondary data. Findings: Mediator neutrality has no consistent or comprehensible meaning and is not capable of coherent application. Requirements for mediator neutrality encourage covert influencing tactics by mediators which itself threatens party autonomy. Mediator intervention ensures ethical and moral implementation of justice, removal of epistemological implications of subjective fairness and compensation for lack of pure procedural justice in the mediation process. Party autonomy requires mediators to intervene ensuring parties adequately informed of the law and equal balance of power. Research limitations/implications: Peer-reviewed journals and secondary data give meaningful insight into perceptions, opinions and beliefs concerning mediator neutrality, party autonomy and fair outcomes. These data comprised unstructured-interviews and questionnaires containing "open-ended" questions. Practical implications: Mediator neutrality and party autonomy are less important than fair settlements. Social implications: Mediator neutrality should be given a contextual meaning; mediation should be more transparent affording the parties opportunity to select a particular type of mediator; transformative and narrative approaches to mediation should be further developed. Originality/value: This paper exposes the myth of mediator neutrality – a popular concept demanded by and anticipated by the parties but which is practically impossible to deliver. It also shows the need for mediator intervention to ensure a fair outcome.